POPULATION ANALYSIS OF THE LOCAL ENDANGERED PŘEŠTICE BLACK-PIED PIG BREED - Emil Krupa; Zuzana Krupová; Eliška Žáková; Radovan Kasarda; Alena Svitáková (Poljoprivreda, 2015)
The pedigree analysis of the local endangered Přeštice Black-Pied pig breed (n=19 289) was performed. Animals born within the period 2012-2014 were assumed as the reference population (n=1 374). The pedigree completeness index reached 100% for four generations back. The 100 % of the genetic pool was explained by 66 ancestors. Although all animals of the reference population were inbred, 57% of them had inbreeding less than five percent. Average inbreeding, co-ancestry coefficient and rate of inbreeding reached 4.93%, 13.48% and 1.29% in reference population, respectively. The effective population size calculated by four different methods varied from 32 to 91 animals in 2014. Average generation interval, average family size for sire and dam parents was 2.5, 17.46 and 6.5 animals, respectively. Total number of founders, effective number of founders, effective number of founders’ genomes and effective number of non-founders genomes reached values 299, 98.05, 21.92 and 28.23 founders, respectively. The average genetic diversity (GD) loss was 13.71% in reference population. The GD loss has increased within the last three year period mainly due to the random genetic drift (77.6%) and by unequal contribution of founders (22.4%). The Preštice Black-Pied breed is highly endangered with GD loss. Mating of closely related animals has to be prevented in breeding and mating program of this breed.